2014
DOI: 10.1155/2014/701839
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Variant (Hemoglobin Aalborg) Mimicking Interstitial Pulmonary Disease

Abstract: Hemoglobin Aalborg is a moderately unstable hemoglobin variant with no affiliation to serious hematological abnormality or major clinical symptoms under normal circumstances. Our index person was a healthy woman of 58, not previously diagnosed with hemoglobinopathy Aalborg, who developed acute respiratory failure after a routine cholecystectomy. Initially she was suspected of idiopathic interstitial lung disease, yet a series of tests uncovered various abnormal physiological parameters and set the diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Despite the low peripheral oxygen saturation, oxygen unloading to the tissue is considered normal with no negative effects such as tissue hypoxia [6]. One study looking at six adult family members with hemoglobin Aalborg reported a concordant low peripheral and arterial oxygen saturation as well as low diffusion capacity for carbon monoxide [3]. Our patient had a high arterial and a low peripheral oxygen saturation on blood gas analysis, as well as a normal DLCO.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Despite the low peripheral oxygen saturation, oxygen unloading to the tissue is considered normal with no negative effects such as tissue hypoxia [6]. One study looking at six adult family members with hemoglobin Aalborg reported a concordant low peripheral and arterial oxygen saturation as well as low diffusion capacity for carbon monoxide [3]. Our patient had a high arterial and a low peripheral oxygen saturation on blood gas analysis, as well as a normal DLCO.…”
Section: Discussionmentioning
confidence: 72%
“…Hemoglobin Aalborg has a reduced oxygen affinity due to the altered state of the hemoglobin molecule in the tense and relaxed state [3,6]. This change shifts the oxygen dissociation curve to the right with an increase in the P50.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hb Aalborg is moderately unstable and is associated with mild anemia [4]. In addition, Hb Aalborg has a reduced oxygen affinity due to the altered state of the Hb molecule in the tense and relaxed state [5,6]. This change shifts the oxygen dissociation curve to the right with an increase in the p50.…”
Section: Figurementioning
confidence: 99%
“…A few years ago, Panou et al [5] reported a Hb Aalborg patient who developed acute respiratory distress syndrome (ARDS), such as interstitial lung disease (ILD)-like clinical symptoms after cholecystectomy surgery. They reported that six out of seven cases caused 59.0-76.0% of %DLCO decrease and found no pulmonary disease.…”
Section: Figurementioning
confidence: 99%